2011
DOI: 10.2147/ijn.s23530
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-erythromycin complexes as a drug delivery device for orthopedic application

Abstract: Background Erythromycin, a hydrophobic antibiotic used to treat infectious diseases, is now gaining attention because of its anti-inflammatory effects and ability to inhibit osteoclasts formation. The aim of this study was to explore a cyclodextrin-erythromycin (CD-EM) complex for sustained treatment of orthopedic inflammation. Methods and results Erythromycin was reacted with β-cyclodextrin to form a nonhost-guest CD-EM complex using both kneading and stirring approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…In addition, the peak at 2θ value of 22.8° in TiO 2 /γCD XRD pattern confirmed that the γCD molecules were successfully attached onto TiO 2 surface . Furthermore, the broad diffraction peaks in the TiO 2 /γCD NPs are due to the presence of abundant oxygen-containing functional groups on TiO 2 NPs . These results clearly exhibited that the γCD molecules were successfully cross-linked to the TiO2 NPs.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…In addition, the peak at 2θ value of 22.8° in TiO 2 /γCD XRD pattern confirmed that the γCD molecules were successfully attached onto TiO 2 surface . Furthermore, the broad diffraction peaks in the TiO 2 /γCD NPs are due to the presence of abundant oxygen-containing functional groups on TiO 2 NPs . These results clearly exhibited that the γCD molecules were successfully cross-linked to the TiO2 NPs.…”
Section: Resultsmentioning
confidence: 61%
“…42 Furthermore, the broad diffraction peaks in the TiO 2 /γCD NPs are due to the presence of abundant oxygen-containing functional groups on TiO 2 NPs. 43 These results clearly exhibited that the γCD molecules were successfully cross-linked to the TiO2 NPs.…”
Section: Resultsmentioning
confidence: 74%
“…That list includes saurolactam, enoxacin, bisenoxacin, concanamycin A, bafilomycin A1, erythromycin, tetracycline, oxytetracycline, and brefeldin A. [26][27][28][29][30][31][32] From this list erythromycin, specifically erythromycin complexed to a cyclodextrin carrier, returns a hit when "joint" and "arthritis" terms are also entered in the search query. In addition to inhibiting osteoclast formation, erythromycin complexed to cyclodextrin showed a longer lasting bactericidal action than uncomplexed erythromycin, thereby demonstrating potential for periprosthetic inflammation reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The cell culture medium was then replaced with fresh culture medium supplemented with various nanofibers (1 mg/mL) for 24 h after cell seeding. Cell toxicity was determined by measuring the release of lactate dehydrogenase (LDH) from membrane integrity-compromised cells into the culture medium at different time points using a Cytotoxicity Detection Kit (Roche Diagnostics GmbH, Mannheim, Germany) following the manufacturer's instructions (Song et al 2011). Briefly, 100 μL of culture medium was added into a plate of 96 wells, mixed with 100 μL working solution, and incubated at room temperature for 30 min in the dark.…”
Section: Cell Culture and Cytotoxicity Assaymentioning
confidence: 99%